2020
DOI: 10.1177/0883073820924213
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Dysfunction and Sleep-Disordered Breathing in Children With Myasthenia Gravis

Abstract: Objectives: The purpose of this study was to prospectively evaluate sleep patterns and the presence of sleep-disordered breathing in children with myasthenia gravis. We further aimed to examine the relationship between sleep and daytime respiratory function using spirometry tests including upright and supine forced vital capacity, sniff nasal inspiratory pressure, and maximal inspiratory pressure. Methods: Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…VATS, as a minimally invasive surgery which has been widely applied for the treatment of thoracic diseases, can visualize patients' thorax clearly on a television screen through a high-definition camera, so the surgeon can conduct the surgery by viewing a television screen, with the advantages of wide range of lesion resection and high safety [ 20 , 21 ]. Some studies reveal that the thymusectomy not only removes the thymus but also effectively clears the fat of anterior mediastinum, but VATS is limited by the surgical field during the resection of the fat of anterior mediastinum, so the surgical procedure should be finished by experienced operators [ 22 , 23 ]. In this study, after the combination therapy was implemented in MG patients, the overall response rate in the experimental group was significantly higher than that in the control group ( P < 0.05), demonstrating that the combination therapy has significantly better efficacy than VATS alone in relieving myasthenic symptoms and improving prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…VATS, as a minimally invasive surgery which has been widely applied for the treatment of thoracic diseases, can visualize patients' thorax clearly on a television screen through a high-definition camera, so the surgeon can conduct the surgery by viewing a television screen, with the advantages of wide range of lesion resection and high safety [ 20 , 21 ]. Some studies reveal that the thymusectomy not only removes the thymus but also effectively clears the fat of anterior mediastinum, but VATS is limited by the surgical field during the resection of the fat of anterior mediastinum, so the surgical procedure should be finished by experienced operators [ 22 , 23 ]. In this study, after the combination therapy was implemented in MG patients, the overall response rate in the experimental group was significantly higher than that in the control group ( P < 0.05), demonstrating that the combination therapy has significantly better efficacy than VATS alone in relieving myasthenic symptoms and improving prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the only previously reported case of MuSK+ MG presenting with severe OSA (AHI of 31/hour), the patient had concurrent bulbar dysfunction as part of their presentation, something not observed in our case initially. An increased prevalence of sleep disordered breathing/ OSA has been reported in some studies including patients who are AChR antibody positive as well as in children with MG (8,9); however, not all studies have found this association (10). In a recent single-center study, the risk of OSA in MG patients was associated with the same risk factors as the overall population, including male sex and obesity (11).…”
Section: Discussionmentioning
confidence: 96%
“…Spirometry test is a simple but useful method for quantitative assessment and management of a variety of pulmonary conditions [ 26 ]. MG is an autoimmune disease characterized by weakness of various groups of skeletal muscles including respiratory muscles, resulting in impaired lung function [ 27 ]. Several previous studies had revealed that decreased lung function parameters were related to POMC or prolonged ventilation support [ 9 , 10 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%